2016
DOI: 10.1155/2016/6209671
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Moderate Intensity Interval Training as an Index of Autonomic Nervous Activity

Abstract: The purpose of this study was to examine the effects of moderate intensity interval training from the change of the autonomic nervous activity. Ten male volunteers aged 21-22 years were studied. After 10-minute rest in a seated position, the subjects were asked to perform the strength of moderate cycling exercise in ergometer. Cycling rate was done in 50 times/min. Load resistance of the ergometer was set to 2.0 kgm. Subjects paused the exercise when the heart rate becomes 120 beats/min. Subjects have resumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…184 Change in gut microbiota during physical exercise might also induce additional anti-inflammatory effects. 185 Regular physical activity also leads to increased vagal tone 186,187 and decreased expression of inflammatory markers, 187 although recent studies provide conflicting results or suggest reduction in circulatory apoptosis marker 112,188 , an effect correlating with high cardiorespiratory fitness. 185 Ursodeoxycholic acid and lithocholic acid have been recently shown to have anti-inflammatory properties by decreasing the release of proinflammatory cytokines while increasing macrophage release of anti-inflammatory cytokines.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…184 Change in gut microbiota during physical exercise might also induce additional anti-inflammatory effects. 185 Regular physical activity also leads to increased vagal tone 186,187 and decreased expression of inflammatory markers, 187 although recent studies provide conflicting results or suggest reduction in circulatory apoptosis marker 112,188 , an effect correlating with high cardiorespiratory fitness. 185 Ursodeoxycholic acid and lithocholic acid have been recently shown to have anti-inflammatory properties by decreasing the release of proinflammatory cytokines while increasing macrophage release of anti-inflammatory cytokines.…”
Section: Inflammationmentioning
confidence: 99%
“…185 Ursodeoxycholic acid and lithocholic acid have been recently shown to have anti-inflammatory properties by decreasing the release of proinflammatory cytokines while increasing macrophage release of anti-inflammatory cytokines. 185 Regular physical activity also leads to increased vagal tone 186,187 and decreased expression of inflammatory markers, 187 although recent studies provide conflicting results or suggest reduction in circulatory apoptosis marker 112,188 , an effect correlating with high cardiorespiratory fitness. 189 This scenario might also involve a neurohormonal mechanism with vagal-mediated gallbladder emptying before exercise.…”
Section: Inflammationmentioning
confidence: 99%
“…Nevertheless, slow breathing in the supine position does not stimulate vagal nerve activity, but stimulates sympathovagal balance activity. However, the load is low, and in the previous study, the ln LF/HF ratio in the resting position was around 2 [ 1 ], and the ln LF value in the resting supine position was in the range of 3.7 to 7.2 [ 2 7 ]. The sitting ln LF value is in the range 5.2-7.7 [ 5 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is desired to develop a method for activating cardiac ANS activity. Previous studies have reported that cardiac ANS activity is enhanced by interval training and slow breathing exercise [ 1 , 8 ]. However, disuse disorders occur due to aging; it is necessary to ensure safety and security by appropriate methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation